The effects of early combined training on the physical development of preterm infants with different gestational ages - He, Fang; Wu, Na; Ma, Xiuwei; Liu, Xiaofang; Gao, Ming; Feng, Zhichun (Frontiers in Pediatrics, 2023)
Objective: To investigate the effects of early compound training on the physical development of preterm infants of different gestational ages. Methods: A total of 144 preterm infants from our hospital’s neonatal intensive care unit (NICU) between 2019 and 2020 were selected as the research participants and randomly divided into an intervention group (77 cases) and a control group (67 cases). The physical development and catch-up growth satisfaction rate of preterm infants in the intervention and control groups were compared at 40 weeks, three months, six months and 12 months of corrected age. Results: At 40 weeks of gestational age and corrected three months of gestational age, the physical growth indexes of the intervention group were higher than those of the control group, with a statistical difference (P<0.05). At the corrected age of 12 months, the body weight and length of preterm infants in the <29 weeks intervention group were still higher than those in the control group (P<0.05). The body weight of preterm infants in the 29–32 weeks and 32–34 weeks intervention groups was higher than in the control group (P<0.05). There was no statistical difference between the intervention and control groups in the 34–37 weeks category (P>0.05). The catch-up growth satisfaction rates of body weight and head circumference in the intervention group were higher than those of the control group at the corrected three months for all the gestational ages (P<0.05). Conclusion: Early compound training can promote the early catch-up growth of preterm infants, especially in the early gestational age groups (<32 weeks), and the catch-up growth promotion can last for 12 months.